Welfare incentives and socio-demographic determinants of self-rated well-being in Malaysia / Ahmad Izzam Mohd Fimi and Rohana Kamaruddin. - Mohd Fimi, Ahmad Izzam; Kamaruddin, Rohana (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Malaysia, among other countries around the world investing immense sum of money to improve social welfare systems by offering social safety net for the deserving ones that exposed to global uncertainties due to economic slowdown. As part of the government initiative to boost the well-being, this study focus on BRIM (1Malaysia Peoples’ Aid), KRIM (1Malaysia People’s Grocery Store), BBIM (1Malaysia Book Voucher) and KIM (1Malaysia Clinics) under Government Transformation Programme (GTP). Specifically, the motivation of this study to identify the most effective and preferred welfare incentives as well as the most significant incentives together with socio-demographic determinants using self-rated well-being by employing logistic regression analysis. Findings discov-ered that K1M has the highest mean (4.94) while the most preferred welfare incentives were BR1M (42%). As for logistic regression analysis, the finding shows that BR1M, KR1M and K1M were significant to influence well-being of people. As comparison, the most significant welfare incentive was BR1M as it has the most significant value at p-value 0.004 and the highest odds ratio at 4.689. Overall, these results suggest that people perceived BR1M as instant relief towards high cost of living and can affects their well-being without considering the socio-demographic backgrounds.